Self-Recording of a National Disaster: Oral History and the Palestinian Nakba - Sayigh, Rosemary (Journal of Holy Land and Palestine Studies, 2020)
It was the stated belief of Zionist leaders that Palestinians expelled from Palestine in 1948 would forget their country within one or two generations. This has not happened and it is therefore a question for research through what relationships and social processes memories of the original land, and the way of life within it, have been produced and reproduced over more than seventy years. This paper is based on interviews as well as participant observation in two camps, Shateela and Bourj al-Barajneh near Beirut (Lebanon), augmented by email interviews with a wider range of Palestinian subjects, both geographically and socially.